Resilience : reflections on the burdens and gifts of facing life's adversities - Edwards, Elizabeth, 1949- (New York : Broadway Books, 2009)
She's one of our most beloved political figures, and on the surface, seems to have led a charmed life. Beautiful family, thriving career, loving marriage. But she's no stranger to adversity. Many know of the strength she had shown after her son was killed in a car accident. She would exhibit this remarkable grace and courage again when the very private matter of her husband's infidelity became public fodder. And her own life has been on the line: days before the 2004 presidential election--when her husband was running for vice president--she was diagnosed with breast cancer. After much treatment the cancer went away-- only to reoccur in 2007. On the campaign trail, Elizabeth met others who have had to contend with serious adversity, and here she draws on their experiences as well as her own, crafting an unsentimental and inspirational meditation on the gifts we can find among life's biggest challenges.-- From publisher description
Keywords: Edwards, Elizabeth, 1949-; Edwards, Elizabeth, 1949- -- Philosophy; Edwards, John, 1953 June 10-; Edwards, John,1953 June 10- -- Family; Resilience (Personality trait); Legislators' spouses -- United States -- Biography; Cancer -- Patients -- United States -- Biography; Lawyers' spouses -- North Carolina -- Biography; North Carolina -- Biography